Nematicidal potential of oilcake agains plant nematodes associated with Coriandrum sativum L. in Balochistan, Pakistan (Bangladesh Journal of Scientific and Industrial Research, 2021)
Ten geneta of plant nematode associated with coriander (Coriandrum sativum L.) were isolated and identified in ten different localities of Balochistan, Pakistan. The most common was Meloidogyne javanica followed by Basiria spp. Principal component analysis (PCA) and cluster analysis using Ward’s method were performed. The results of the two methods supported each other. Castor and mustard oilcakes and carbofuran, a chemical nematicide were used in treatments against Hoplolaimus Columbus and M. javanica larvae. Mustard oilcake was found to be more effective on H. Columbus while castor oilcake showed effective control on M. javanica.Bangladesh J. Sci. Ind. Res.56(1), 61-68, 2021